Facebook vs moodle : Surveying university students on the use of learning management systems to support learning activities outside the classroom - Gomes, Luis Mendes (2015)
CISTI'2015 - 10ª Conferência Ibérica de Sistemas e Tecnologias de Informação, 17 a 20 de junho de 2015, Águeda, Aveiro, Portugal.